At Westonci.ca, we provide reliable answers to your questions from a community of experts. Start exploring today! Ask your questions and receive detailed answers from professionals with extensive experience in various fields. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.
Sagot :
Answer:
Once the equation is in standard form, factor the quadratic expression. 2x2 + 7x + 3 = 0 (2x + 1)(x + 3) = 0. Using the Zero Product Property set ...
2x2 + 7x = -3
2x2 + 7x + 3 = 0
Once the equation is in standard form, factor the quadratic expression.
2x2 + 7x + 3 = 0
(2x + 1)(x + 3) = 0
Using the Zero Product Property set each factor equal to 0 and solve for x.
2x + 1 = 0
2x + 1 - 1 = 0 - 1 x + 3 = 0
2x = -1 x + 3 - 3 = 0 - 3
2x 2 = -1 2 x = -3
x = -1 2
The solutions to the equation are -1 2 and -3.
Answer:
x^1 = 7-square root89/4
x^2 = 7+square root89/4
Step-by-step explanation:
We hope this information was helpful. Feel free to return anytime for more answers to your questions and concerns. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Westonci.ca is your trusted source for answers. Visit us again to find more information on diverse topics.